The Role of Kiai and Blater in the Regional Election in Madura: Discourse on Legal Culture - Khoiri, Ach.; Zakaria, Avien; Ulumuddin, Ihya; Lana, Muhammad Ahsin; Islam, Ach Robithul (Faculty of Law Universitas Trunojoyo Madura, 2024)
This study aims to analyse the implementation of elections in Madura, which should be an arena to elect leaders who are expected to bring change and improvement in Madura but cannot be adequately maximised. There is even an impression that implementing elections only perpetuates the power of informal rulers in Madura, namely kiai and blater. This research contributes to describing the various weaknesses of the election regulation applied in Madura with the hope that all these weaknesses can be anticipated and will help reform the election regulation model in Indonesia. This research uses empirical legal research methods with socio-legal and anthropo-legal approaches. This research found that election regulations cannot overcome the community's need to choose prospective leaders in Madura honestly and according to their conscience. This is supported by the fact that in every election, contestants supported by kiai and blater are almost certain to win the contestation of regional elections in Madura.